2011
DOI: 10.1177/0034355210396948
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Rural Vocational Rehabilitation Clients Who Leave the System Prematurely: A Qualitative Exploration

Abstract: Vocational rehabilitation (VR) clients who leave the system prematurely experience worse employment outcomes than clients who stay in services. The authors conducted this study to learn about factors leading to premature exit by rural VR clients. Results will inform survey development for a large longitudinal study on this topic. The authors content coded 27 qualitative telephone interviews with former rural VR clients who exited the system prematurely. Reported reasons for premature exit included (a) discrepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Conversely, disengagement or premature exit from a health or human service delivery system can cause significant losses including, but not limited to, a poor return on investment (Lequerica, Donnell, & Tate, 2009; Lequerica & Kortte, 2010; Medley & Powell, 2010). Approximately 50% of clients served by the state-federal vocational rehabilitation (VR) program exit prior to completion of services, and in fiscal year 2009, US$325 million of VR funds were expended for cases closed due to refusal of services, clients’ failure to cooperate, or an agency’s inability to locate the client (Rigles, Ipsen, Arnold, & Seeking, 2011). Researchers, practitioners, and policy makers are beginning to assess the treatment goal of engagement as a variable to gauge client motivation, contain costs, and improve the effectiveness of intervention strategies (Prendergast, Podus, Chang, & Urada, 2002; Simpson, 2004).…”
mentioning
confidence: 99%
“…Conversely, disengagement or premature exit from a health or human service delivery system can cause significant losses including, but not limited to, a poor return on investment (Lequerica, Donnell, & Tate, 2009; Lequerica & Kortte, 2010; Medley & Powell, 2010). Approximately 50% of clients served by the state-federal vocational rehabilitation (VR) program exit prior to completion of services, and in fiscal year 2009, US$325 million of VR funds were expended for cases closed due to refusal of services, clients’ failure to cooperate, or an agency’s inability to locate the client (Rigles, Ipsen, Arnold, & Seeking, 2011). Researchers, practitioners, and policy makers are beginning to assess the treatment goal of engagement as a variable to gauge client motivation, contain costs, and improve the effectiveness of intervention strategies (Prendergast, Podus, Chang, & Urada, 2002; Simpson, 2004).…”
mentioning
confidence: 99%
“…In a survey of vocational rehabilitation consumers (Ipsen & Goe, 2016), almost half of the respondents reported that the rehabilitation process was too slow. Perceived or actual delays in services, either at application or in service delivery, may result in consumers feeling less engaged in the process and exiting the system before their cases can be successfully closed (Ipsen & Goe, 2016; Rigles et al, 2011). In a study of Social Security Disability Insurance (SSDI) recipients applying for vocational rehabilitation services, Honeycutt and Stapleton (2013) found wide variations in wait times from application to IPE across states.…”
mentioning
confidence: 99%